Improving children’s self-esteem and perceived social related abilities: the evaluation of a school-based program (Italian Journal of Public Health, 2006)
Background and Objective: Health education programmes delivered in school settings are often design toenhance child self–esteem or various social skills in order to improve the way that they interact in every daylife. Although these are becoming increasingly frequent, little is known about the real efficacy of many of theavailable programs that claim to be able to positively develop these psychological dimensions. This study,which takes a Public Health approach, examines the effect of a school-based educational programme,designed following the WHO recommendations, in order to favour children’s self-esteem and improveperceived socio-relational competences.Method: To test the effectiveness of this intervention, a non randomized, controlled, prospective study wasset up. All 291 eligible students, aged between 8-10 years, were enrolled. To assess self-esteem andperceived supportive relationship, a well-known and descriptive scales were utilised (MSCS, SPPC, AIR).Results: No difference was found between the experimental and control groups with respect to the children’sself-esteem and perceived socio-relational competences following the intervention, except in the quality of theirrelationships with their teachers, which improved in the experimental group and declined in the control group.Discussion: The educational programme used in our study did not seem to be able to enhance self-esteemin the intervention group, but the methodological instruments used to monitor the change in self-esteemdomonstrated a different rate of change in the more disadvantaged sub-groups of the observed population.
Keywords: self-esteem; school program; program evaluation